PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP DISIPLIN KERJA KARYAWAN PT. POSMETRO MANDAU - Yapentra, Arhipen (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
The purpose of this research is to know the influence of leadership and motivation to work discipline of PT. Posmetro Mandau Duri. Population in this research is all employees of PT. Posmetro Mandau Duri with 38 employes. Thus the sample in this study taken entirely, because the population is relatively little or less than 100. The research method used is multiple linear regression test, test coefficient determination and Test F. The results of this study is simultaneously leadership and motivation have a significantinfluence on the discipline of work with signification rate is 0.003. While the leadership by partial has a significant effect on the discipline of work, but motivation has no significant effect on employee work discipline of PT. Posmetro Mandau Duri